Customization and Personalization in Luxury Marketing : Understanding Consumer Perceptions and Industry Trends. - Hardiyanti, Widya; Olšanová, Květa; Zlatić, Marija; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis explores the role of evolving customization and personalization strategies in luxury marketing, focusing on customer experiences and industry professional insights. Using qualitative research methods, the study examines tangible personalization and customization experience (e.g.,monogramming and engraving). The findings of this study will not only enrich our understanding of the tools and strategies employed by luxury brands but will also provide valuable insights into the motivation, perceptions, challenges to appeal to future customers.
Vedoucí práce: Květa Olšanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses